Fourth Representative of The Babylonian Dynasty - Sobirov Jamshidbek Zokirjon O'g'li (Global Scientific Publishing, 2022)
This article discusses the birth, naming, life activities of Shaʹdrach, Meʹshach and A·bedʹne·go, their contribution to expanding the territory of the Babylonian Empire, their role in the rise of painting, and the reasons for the naming of Nurjahon, the wife of Shaʹdrach, Meʹshach and A·bedʹne·go.
Keywords: Muhamamad Salim; Shaʹdrach; Meʹshach and A·bedʹne·go